Antibiofilm property and multiple action of peptide PEW300 against Pseudomonas aeruginosa - Wang, Meng; Deng, Zifeng; Li, Yanmei; Xu, Keyong; Ma, Yi; Yang, Shang-Tian; Wang, Jufang (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa (P. aeruginosa), an opportunistic pathogen, is often associated with difficulties in treating hospital-acquired infections. Biofilms formed by P. aeruginosa significantly improve its resistance to antimicrobial agents, thereby, posing a great challenge to the combat of P. aeruginosa infection. Antimicrobial peptides (AMPs) have recently emerged as promising antibiofilm agents and increasingly attracting the attention of scientists worldwide. However, current knowledge of their antibiofilm behavior is limited and their underlying mechanism remains unclear. In this study, a novel AMP, named PEW300, with three-point mutations (E9H, D17K, and T33A) from Cecropin A was used to investigate its antibiofilm property and antibiofilm pathway against P. aeruginosa. PEW300 displayed strong antibacterial and antibiofilm activity against P. aeruginosa with no significant hemolysis or cytotoxicity to mouse erythrocyte and human embryonic kidney 293 cells. Besides, the antibiofilm pathway results showed that PEW300 preferentially dispersed the mature biofilm, leading to the biofilm-encapsulated bacteria exposure and death. Meanwhile, we also found that the extracellular DNA was a critical target of PEW300 against the mature biofilm of P. aeruginosa. In addition, multiple actions of PEW300 including destroying the cell membrane integrity, inducing high levels of intracellular reactive oxygen species, and interacting with genomic DNA were adopted to exert its antibacterial activity. Moreover, PEW300 could dramatically reduce the virulence of P. aeruginosa. Taken together, PEW300 might be served as a promising antibiofilm candidate to combat P. aeruginosa biofilms.